THE MYSTICAL TEACHING OF KHOJAGAN ABOUT THE “UNIVERSE OF THE GREAT” (Scientific journal of the Fergana State University, 2024)
In this article, the improvement and wide spread of the Khojagan Sufi order, the development after the founder of this Sufi order, Abdulkhaliq Gijduvani, and the philosophical analysis of their activities in the order are made. On the basis of Khojai Jahan's spiritual heritage, great people were brought up. Among them, Khwaja Ahmad Siddiq, Khwaja Avliyoi Kabir, Khwaja Arif Revgari, Khwaja Bahauddin Naqshband and many others received spiritual blessings from him. In Silsila, the deposit - the sheikh's permission - was handed over to Khoja Arif Revgari by his caliphs. In this sense, the spiritual legacy of Abdukholiq Gijduvani is reflected in one of the spiritual treasures that will serve our young people who are laying the foundations of the Third Renaissance in New Uzbekistan